TIERED LOYALTY PROGRAM: SYSTEMATIC LITERATURE REVIEW (SLR) AND BIBLIOMETRIC ANALYSIS OF DIMENSIONS, ANTECEDENTS, AND OUTCOMES (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Multi-tier loyalty programs (MTLPs) have become a dominant strategic instrument for customer retention and value creation, yet the literature remains fragmented with limited systematic synthesis. This study aims to comprehensively review and map the research landscape of MTLPs by identifying core dimensions, antecedents, outcomes, moderating factors, and research gaps. Employing a Systematic Literature Review (SLR) following PRISMA 2020 protocol integrated with bibliometric analysis using VOSviewer, this research systematically searched Scopus, Web of Science, and Google Scholar for publications from 2022 to 2026. From 1,247 initial records, 29 articles met the inclusion criteria for final synthesis. The analysis reveals eight interrelated dimensions of MTLPs Tiered Structure, Differential Rewards, Customer Segmentation, Dynamic Engagement, Perceived Value & Aspirational Goals, Retention Targeting, Spending Pattern Evolution, and Aspirational Status & Psychological Ownership which are influenced by five antecedents (Consumer Behavior, Service Design, Marketing Strategy, Digital Technology, and Brand Perception) and moderated by three factors (Industry Context, Consumer Demographics, and Digital Infrastructure). Five primary outcomes were identified: Customer Retention, Customer Lifetime Value, Brand Loyalty, Share of Wallet, and Word-of-Mouth & Advocacy. Bibliometric mapping uncovers six critical research gaps: limited longitudinal studies, insufficient psychological mechanism understanding, unexplored AI/ML integration, lack of evidence-based tier structure optimization, minimal cross-cultural analysis, and under-researched unintended consequences including loyalty fatigue and privacy concerns. This study contributes an integrated conceptual framework connecting MTLPs dimensions with their antecedents, moderators, and outcomes, offering both theoretical enrichment for academic discourse and evidence-based practical guidelines for program designers across industries.